Perancangan Pondok Pesantren dengan Pendekatan Arsitektur Sustainable - Annisa Nila Sakinah; Ahmad Ridho (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This research aims to design an Islamic Boarding School (Ponpes) with a sustainable architecture approach that is able to answer environmental, social, and economic challenges holistically. The method used is a qualitative-descriptive approach through architectural design research, which combines empirical data from the field with theoretical studies from relevant literature. The design location is on Jl. Gunungpati Raya, Nongkosawit Village, Gunungpati District, Semarang City, with an area of ±19,909.77 m². Data collection techniques include literature study, site observation, and comparative design study. Data were analyzed descriptively and spatially to formulate user needs and site potential. The design results show that the sustainable architecture approach can be implemented through functional layout, passive energy utilization, vegetation preservation, rainwater management, and waste recycling system. The design also accommodates social and economic aspects through the provision of organic farming areas and small farms as part of practice-based education. Contemporary Islamic architectural aesthetics are applied contextually, creating a healthy, inclusive, and adaptive learning environment. This research produces a sustainable pesantren design concept that can be a reference model in the development of environmentally friendly and self-reliance-based Islamic educational institutions..